Impact of agroforestry systems on the soil organic matter: A carbon and nitrogen modeling - Vilela, Emerson Ferreira; Mendonça, Eduardo Sá (Coffee Science - ISSN 1984-3909, 2014)
The simulation models are essential tools to study the soil organic matter dynamic and the transformation of its pools in tropical soils. The aim of this study was to adjust the CENTURY model for the conditions of agroflorestry systems (coffee intercropped with Ingá) developed in the Zona da Mata of Minas Gerais simulating the dynamic of organic matter, comparing the total organic carbon (OC) and nitrogen (N) stocks in different pools (active, slow and passive). The studied area, originally under Atlantic Forestry, was deforested in 1957 and left as pasture (during 23 years), after this period was cultivated with rice and beans (for 7 years). Nowadays, part of the area is under coffee (coffea arabica) in agroflorestry system and the other one is under conventional coffee. The coffee plantation was performed in 3.0 x 1.0 m spacing. The active pool was represented by the microbial biomass, the light fraction was used as estimative of the slow pool, and the passive pool was calculated by the difference between of total organic C and the active and slow pools together. The values simulated by the model were able to estimate the impact of agroforestry system on the soil organic matter. The studied agroforestry system was not able to recuperate the soil C and N stocks. The microbial C and the light-fraction C were more sensible to the impact of the agroforestry system on the soil organic matter. The Century model presented great potentiality to simulate the C and N dynamic in complex tropical agroforestry systems.